Zambian women take the lead in adapting food systems to climate change - Caroli, Giulia; Maviza, Gracsious; Maphosa, Mandlenkosi; Fumpa-Makano, Rosemary (2025)
Women’s contributions in food systems are often unpaid, undervalued and overlooked. And the necessity of climate adaptation now imposes further burdens on them to overcome. Agricultural transformation is often technocratic and top-down, with little to no attention to women’s issues and gender equality. Also, these women are often depicted as “passive victims” rather than agents of change in realising plans for climate-resilient and sustainable food systems. We spent time in the southern province of Zambia in April 2023 and in December 2024, conducting participatory research on these very questions. What we discovered strongly challenges these paradigms. Not only are women in Southern rural Zambia collaborating and innovating to adapt to climate shocks, but these successful strategies have also inspired men in the community, forming a crucial layer of community resilience.